Case Report: Area of focus in a case of giant aortic arch pseudoaneurysm following fish bone penetration - Xiong, Jianxian; Cao, Jiaxin; Yu, Junjian; Li, Peijun; Zeng, Zitao; Pan, Xudong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundEsophageal foreign body impaction represents a common clinical emergency. In severe cases, it can lead to esophageal perforation and aortic injury, potentially causing life-threatening aorto-esophageal fistulas. While immediate intervention is critical, concurrent infection and retained foreign material substantially complicate management.Case PresentationWe report a rare case of a giant aortic arch pseudoaneurysm secondary to a migratory fish bone. Contrast-enhanced computed tomography (CT) confirmed the diagnosis, prompting urgent surgery. Median sternotomy under cardiopulmonary bypass enabled simultaneous foreign body extraction and aortic perforation repair using autologous pericardium. We reconstructed the aortic arch using a branched stent-graft system via the frozen elephant trunk (FET) technique. Postoperatively, systematic mediastinal irrigation, proactive gastrointestinal decompression, and protocolized enteral nutritional support facilitated complete recovery without requiring secondary esophageal reconstruction.ConclusionAortic injuries resulting from esophageal foreign bodies frequently necessitate a multidisciplinary approach. This case demonstrates the feasibility of a single-stage surgical strategy combining aortic repair via the frozen elephant trunk technique with conservative, non-operative management of the concomitant esophageal injury, facilitated by rigorous postoperative care. Treatment strategies must be individualized based on a comprehensive assessment of the aortic involvement pattern, anatomical location, and coexisting pathological conditions.